Bringing E-Money to the Poor : Successes and Failures - Riley, Thyra A. (Washington, DC: World Bank, 2017)
Moving toward universal access to financial services is within reach, thanks to new technologies, transformative business models, and ambitious reforms. Instruments such as e-money accounts and mobile accounts, along with debit cards and low-cost traditional bank accounts, can significantly increase financial access for those who are excluded.